Yesus, Perantau dari Surga: Sebuah Usaha Awal Meninjau Kristologi Injil Yohanes dari Sudut Pandang Imigrasi - Ekaputra Tupamahu (Asosiasi Teolog Indonesia, 2015)
This article registers a preliminary effort to (re)construct Christology in the Gospel of John from a migrant perspective. Jesus is